SITUASI KOMUNIKATIF DARI TRADISI MAKAN SINGKONG PADA PENGANUT KEPERCAYAAN NGAJI DIRI - Dina Alamianti (Dialektika, 2017)
Tradition is a custom which is passed down through generations from one generation to the next generation. The tradition of eating cassava began in 1924. It is a tradition run by adherents of Ngaji Diri in Cireundeu Village Cimahi. The purpose of the study is to express how the communicative situation from consume cassava tradition in the Ngaji Diri belief group. Qualitative methods with ethnography of communication approach used in this study. Technique of data collecting by interview, observation, documentation study, and triangulation. The results revealed that there is differences in the comunicative situation from the tradition of eating cassava at home and at Bale Saresehan. The communicative situation at home and Bale Saresehan is a form created as preservation of custom, a ritual, and a group identity.